Impact of the Economy Digitalization on Welfare in the Developed and Developing Countries - Zvereva, Anna Andreevna; Belyaeva, Zhanna Sergeevna; Sohag, Kazi (Economy of Regions, 2019)
Digitalization is one of the key world economic trends. Countries with the wealthiest economies have integrated the digitalization program into their economic development plans. At the same time, monitoring of the digitalization’s dynamics and degree of impact on welfare is of great importance for all countries of the global community. Nowadays, there are practically no integrated studies assessing institutional, cultural, economic, educational and infrastructural consequences of the digitalization. This article assesses how the digitalization affects the mentioned drivers of social and economic development. Moreover, it examines the digitalization’s impact on welfare of the developed and developing countries. The relevance of defining the effects of digitalization’s rapid implementation in various countries determined the study’s purpose. We based the methodology on building the balanced panel regression. The key metric for measuring the digitalization is the Digital Evolution Index of 50 countries for 2008, 2013 and 2017. The research findings have confirmed positive impact of the digitalization in the developed countries due to a high levels of digital inclusivity, public and private investment, and digital literacy and trust. At the same time, in the developing countries the digitalization’s impact on welfare was not confirmed due to a low level of state involvement in digitalization development and rigid, non-flexible institutional environment. The obtained empirical results can be used for forming management tools of the digitalization strategy for regions with various levels of social, economic, institutional and digital environment development.